Isolation and chemical investigation of bixin from Bixa orellana Linne (Family Bixaceae) - Cruz, Ma. Elizabeth F.
Annatto extract contained in the pericarp of the fruit Bixa orellana (Fam. Bixaceae) is extracted by Soxhlet Extraction using boiling chloroform as the solvent.